Effects of Temporal Heterogeneity of Water Supply and Spatial Heterogeneity of Soil Nutrients on the Growth and Intraspecific Competition of Bolboschoenus yagara Depend on Plant Density - Yu, Hongwei; Shen, Nan; Yu, Dan; Liu, Chunhua (Frontiers in Plant Science, 2019)
Clonal plants may face various types of resource heterogeneity in their natural habitats; as such, spatial or temporal resource heterogeneity can affect the growth of clonal plants. Clonal plants can concentrate their organs in a smaller area where resources are high would cause heterogeneity to increase competition between plants. Most studies on resource heterogeneity have investigated the response of plants under a single density or by manipulating a single resource. Few studies have tested the effects of the heterogeneous distribution of two covariable resources on plant growth and intraspecific competition. A greenhouse experiment was therefore conducted to study plant responses to the spatial and temporal heterogeneity of the soil and water supply under a variety of plant densities (one, two, four or six plants per container). The perennial clonal herb Bolboschoenus yagara was grown under different combinations of water supply patterns, soil nutrient distribution types and plant densities while maintaining the total water and soil nutrient availability per container constant. Compared with that at a relatively high plant density, soil nutrient heterogeneity resulted in significantly less total plant biomass and less-modified morphological traits when the plant density is relative low. At the highest plant density, compared with the homogeneous soil treatments, the heterogeneous soil treatments significantly increased the total biomass and R/S ratio. Water supply patterns also clearly affected plant morphological traits at the highest plant density. Furthermore, soil heterogeneity significantly increased intraspecific competition intensity at low plant densities, but did not significantly affect intraspecific competition intensity at higher plant densities. Water heterogeneity had little impact on intraspecific competition. These results suggest that the growth performance and intraspecific competition of B. yagara are more strongly affected by soil nutrient distribution rather than by water supply patterns and that competition for soil nutrients may increase plant sensitivity to soil heterogeneity.